Mencken : the American iconoclast - Rodgers, Marion Elizabeth (Oxford University Press, 2005)
H.L. Mencken enjoys a reputation as a great newspaper journalist, famous wit, and a figure of controversy. This biography traces his extraordinary life and the great issues he made his own: civil liberty, free speech & the repeal of prohibition.